English Teacher’s Activities in Implementing the Scientific Approach ‎ of the 2013 Curriculum in Teaching and Learning Process ‎ at SMPN 3 Kampar - zul hendri (Journal of Education and Teaching, 2020)
ABSTRACTThis research was aimed to investigate the English teacher’s activities and determining factors in implementing the scientific approach of the 2013 curriculum in teaching and learning process. This research used qualitative research design. The subject of this research was English teacher of SMPN 3 Kampar. The data were collected by using observation sheet, interview, and documentation. The data were analyzed by using data analysis process developed by Creswell (1998): reading, describing, classifying, and interpreting. This research revealed that observing, experimenting, and communicating stages had been implemented very well in each meeting. However, questioning stage was only able to be implemented well. The teacher had provided opportunities for the students to ask some questions by walking over and pointing at the student to ask about the lesson. But, it was only conducted in the first and second meetings. Meanwhile, the implementation of associating stage was still bad. The teacher was only able to do this stage in the third meeting by giving the students task individually. This research also revealed that teacher’s motivation, perception, and experience were internal factors while media and environment were external factors influenced English teacher’s activities in implementing the scientific approach of the 2013 curriculum.